Calculation of the coherent (Rayleigh) and incoherent (Compton) cross section by using CSC model. - Talib Al- Helaly, Mushtaq (Al-Qadisiyah Journal of Pure Science, 2017)
In this research work ,the cross section of coherent scattering "Rayleigh" and incoherent "Compton" for the compound energy range 1keV-50000eV , discuss for W and Cd by employing the equation which is related to "Rayleigh" scattering while program "Compton" scattering ,the cross section has been discuss by Klien-Nishina equation . All these equations obtain by employing CSC(cross section calculations) through language machine of Fortran 90 which provides a high flexibility and extreme accuracy in the calculating many physical parameters such as attenuation and scattering coefficients for any chemical compound or alloys.